2011
DOI: 10.4314/njp.v38i3.72262
|View full text |Cite
|
Sign up to set email alerts
|

Cord care practices among mothers attending immunization clinic at the University of Benin Teaching Hospital, Benin City.

Abstract: In developing countries, individual cases and epidemics of cord infections continue to occur, even in supposedly clean nurseries for newborns. The hazards of poor cord care are not limited to predisposition to infections. There is also the risk of bleeding from the cord which can be rapidly fatal. Empirical observation suggests that harmful traditional cord care practices abound in our community, thus placing newborn babies at risk of morbidity and mortality. In spite of this, there is paucity of data on cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
17
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 0 publications
10
17
2
3
Order By: Relevance
“…Another study carried out in Nigeria by Ambe et al on newborn umbilical cord care revealed that 64% of children's mothers did not attend school; this corresponded to the double of the proportion of unschooled mothers in our study [15]. As regards mothers' occupation, our findings are in consonance with those of Abhulimen-Iyoha et al who identified 38% of resellers, 26% of craft workers and 13.7% of housewives [11] [12]. Several research works performed in the sub-region by different authors on newborn traditional care practices disclosed that housewives were the most represented, thus disagreeing with our study findings [7] [14].…”
Section: Sociodemographic Characteristics Of Population Included In Tsupporting
confidence: 82%
See 3 more Smart Citations
“…Another study carried out in Nigeria by Ambe et al on newborn umbilical cord care revealed that 64% of children's mothers did not attend school; this corresponded to the double of the proportion of unschooled mothers in our study [15]. As regards mothers' occupation, our findings are in consonance with those of Abhulimen-Iyoha et al who identified 38% of resellers, 26% of craft workers and 13.7% of housewives [11] [12]. Several research works performed in the sub-region by different authors on newborn traditional care practices disclosed that housewives were the most represented, thus disagreeing with our study findings [7] [14].…”
Section: Sociodemographic Characteristics Of Population Included In Tsupporting
confidence: 82%
“…Our finding is similar to the one of Abhulimhen-Iyoha et al who studied practices of umbilical cord care in newborns in 2009 at the Benin City University teaching hospital [11] [12]. In contrast, male sex predominated in another study on newborn umbilical cord care carried out by Joel-Medewase et al in Osun State (South-west Nigeria) in 2008; sex ratio was 1.1 [13].…”
Section: Sociodemographic Characteristics Of Population Included In Tsupporting
confidence: 73%
See 2 more Smart Citations
“…Recently, the high-risk approach of conducting tetanus toxoid (TT) Supplementary Immunization Activities (SIAs) targeting women of reproductive age was conducted in three states of the federation and selected Local Government Areas (LGAs) in 5 other states including Borno. Health education to modify harmful cultural practices that directly encourage the risk of acquisition of tetanus is also useful 910. Nigeria plans to achieve elimination in a phased manner by focusing on two zones (South-east and South-west) in 2013-2014 followed by the remaining four zones.…”
Section: Introductionmentioning
confidence: 99%